Experimental study of the hard x-ray emissions in a plasma focus of hundreds of Joules - Barbaglia, Mario Oscar (2009)
An experimental study on hard x-ray production in a small plasma focus device operating in a few hundreds of Joule range is presented. A threshold in the voltage drop on the pinch was observed for x-ray emission. A comparison with Dreicer theory for electrons runaway in plasmas yields significant agreement. The study was performed at a constant pressure (1.8 mbar) of deuterium with three different anode lengths.